PENGARUH PUPUK PELENGKAP CAIR, PUPUK UREA DAN NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) VARIETAS CIHERANG - E Tadjudin; - Alfandi; Diah Ekawati Sulihalialevi Yafenka (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2016)
This study aims to determine: (1) the effect of Complementary Liquid Fertilizer, Urea and NPK on the growth and yield of rice (Oryza sativa L.) Ciherang varieties, (2) the influence of Complementary Liquid Fertilizer, Urea and NPK the most good for growth and yield of rice (Oryza sativa L.) Ciherang varieties, and (3) the correlation between the components of the growth and yield of rice (Oryza sativa L.) Ciherang varieties. The experiment was conducted Kecomberan Villages Talun District Cirebon Regency, from May through the month of August 2015. The method used in this study is the experimental method. The experimental design used a randomized block design (RBD), factorial. The study consisted of two treatment factors were repeated 3 times. The first factor, concentration of complementary liquid fetilizer consists of three levels, namely: K1 (1 cc/Liter per plot), K2 (2 cc/Liter per plot), and K3 (3 cc/Liter per plot). The second factor is dose fertilizer (P) consists of three levels, namely: P1 (Urea 200 kg/ha, NPK 150 kg/ha), P2 (Urea 250 kg/ha, NPK 200 kg/ha), and P3 (Urea 300 kg/ha, NPK 250 kg/ha).